Pharmacoepidemiology and Clinical Correlates of Lithium Treatment for Bipolar Disorder in Asia - Shuy, Yao Kang; Santharan, Sanjana; Chew, Qian Hui; Lin, Shih-Ku; Ouyang, Wen-Chen; Chen, Chih-Ken; Park, Seon-Cheol; Jang, Ok-Jin; Park, Jun Hyuk; Chee, Kok-Yoon; Ding, Kwong Sen; Chong, Jamaline; et al. (Journal of clinical psychopharmacology, 2024)
As clinical practices with lithium salts for patients diagnosed with bipolar disorder (BD) are poorly documented in Asia, we studied the prevalence and clinical correlates of lithium use there to support international comparisons. We conducted a cross-sectional study of use and dosing of lithium salts for BD patients across 13 Asian sites and evaluated bivariate relationships of lithium treatment with clinical correlates followed by multivariate logistic regression modeling. In a total of 2139 BD participants (52.3% women) of mean age 42.4 years, lithium salts were prescribed in 27.3% of cases overall, varying among regions from 3.20% to 59.5%. Associated with lithium treatment were male sex, presence of euthymia or mild depression, and a history of seasonal mood change. Other mood stabilizers usually were given with lithium, often at relatively high doses. Lithium use was associated with newly emerging and dose-dependent risk of tremors as well as risk of hypothyroidism. We found no significant differences in rates of clinical remission or of suicidal behavior if treatment included lithium or not. Study findings clarify current prevalence, dosing, and clinical correlates of lithium treatment for BD in Asia. This information should support clinical decision-making regarding treatment of BD patients and international comparisons of therapeutic practices.